BigBasket.com : redefining the business model - Thomas, Sujo, (SAGE Knowledge. Cases., 2017)
The potential of online grocery retailing in India has seen different players trying out various business models to capture market share and post a healthy growth rate. Among the different players in India's online grocery retailing, BigBasket has evolved into one of the major players. It follows the inventory based model which has been generally criticized due to its high capital requirements. The problem for BigBasket is further compounded, as after securing funding worth USD 150 million from the UAE based Abraaj group, it has to tackle the challenge of the Government of India guidelines which stated that Foreign Direct Investment (FDI) in the inventory based model of e-commerce would not be permitted. This case discusses the online grocery industry in India, the supply chain challenges faced by the industry as well as the opportunities for the industry by predominantly focusing on one of its major players. Various business models followed by the industry are described in detail. Additionally, the case provides a brief background of the existing players in the online grocery retailing market in India, while deliberating upon the ultimate choice of business model for BigBasket to sustain itself in the competitive environment.